Portfolio Manager Compensation in the U.S. Mutual Fund Industry - Ma, Linlin (Institutional Knowledge at Singapore Management University, 2014)
Using a hand-collected data set of over 5,000 mutual funds, we study the compensation structures of individual portfolio managers in the U.S. mutual fund industry. About three-quarters of portfolio managers receive performance-linked bonuses from investment advisors. Managers with performance-linked bonuses exhibit superior subsequent fund performance, especially when advisors link pay to performance over a longer time period. In contrast, alternative compensation arrangements, such as fixed salary, assets-based pay, or advisor-profits-based pay are not associated with superior performance. Overall, our study documents novel empirical evidence on the impact of individual portfolio manager compensation on mutual fund performance.